Membangun Daya Saing Danau Telok Putih Melalui Community Based Tourism - Relli Asmadi; Alditia Detmuliati; Alfitriani (CV. ITTC INDONESIA, 2026)
Lake Telok Putih is one of the natural tourism destinations in Ogan Ilir Regency with considerable potential to be developed through a Community Based Tourism (CBT) approach. However, its development still faces several challenges, including limited tourism facilities and infrastructure, inadequate promotion, and suboptimal community participation. This study aims to analyze the development of Lake Telok Putih as a community-based tourism destination. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings reveal that local community involvement in tourism management has been implemented but has not yet reached its full potential. Development strategies that can be applied include strengthening community participation, improving supporting facilities, optimizing digital promotion, and enhancing collaboration among local communities, tourism managers, and government institutions. These strategies are expected to improve the destination’s competitiveness and support the sustainability of community-based tourism development at Lake Telok Putih. Keywords: Lake Telok Putih, Community Based Tourism, Tourism Development, Community Participation, Sustainable Tourism.